Elevated plasma interleukin-18 is a marker of insulin-resistance in type 2 diabetic and non-diabetic humans - Fischer, Christian P.; Perstrup, Lisbeth B.; Berntsen, Annika; Eskildsen, Peter; Pedersen, Bente K. (Clinical Immunology, 2005)
Elevated plasma IL-18 is present in several conditions sharing insulin-resistance as common trait, but the association with insulin-resistance per se is not established. Plasma/serum IL-6, IL-18, TNF-α, soluble TNF receptor II (sTNFR2), and C-reactive protein (CRP) were measured in 97 patients with type 2 diabetes (DM) and 84 non-diabetic controls (CON). The association with insulin-resistance—estimated using the homeostasis model assessment (HOMA-IR)—was analyzed using multivariate linear and logistic regression. Compared to CON, DM demonstrated higher plasma levels of IL-18 ( P = 0.001), IL-6 ( P < 0.001), sTNFR2 ( P = 0.005), and CRP ( P < 0.001), while TNF-α was lower ( P = 0.017). Plasma IL-18 increased across HOMA-IR quartiles in both DM and CON, both with and without adjustment for confounders (all P < 0.05). In contrast, neither IL-6, TNF-α, sTNFR2, nor CRP was associated with HOMA-IR in CON when adjusting for confounders. Accordingly, 50% increase of IL-18 corresponded to a marked increase of HOMA-IR in both DM and CON (DM: 26%, P = 0.014; CON: 25%, P = 0.003) after adjustment for confounders. Our results show that plasma IL-18 was associated with HOMA-IR independent of obesity and type 2 diabetes.